ANALISIS PENGARUH BELANJA PEMERINTAH, TENAGA KERJA, DAN PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI REGIONAL PROVINSI JAWA TIMUR TAHUN 2010-2015 - Avicenna S Hidayat; Frederic Winston Nalle (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2017)
Regional economic growth is expressed in the Gross Domestic Regional Product is a good indicator in analyzing the economic conditions of a region. East Java is a province with high regional economic growth. This is supported by adequate government spending, labor, and local revenue. In terms of government expenditure that always experienced increase, indicating more activities financed by the government budget so that the expected multiplier effect is also greater. On the other side of the labor force, East Java has great potential, 19, 36 million people by 2015. Finally, in terms of Original Local Government Revenue, in 2015 the percentage of realization of Original Local Government Revenue East Java is even able to exceed the percentage of realization of state revenues derived from taxes. This study aims to determine the effect of government spending, labor, and Original Local Government Revenue on regional economic growth in 38 districts / cities in the Province of East Java period 2010-2015. Using panel data analysis, it was found that government spending, labor, and Original Local Government Revenue variables were positively and significantly influenced regional economic growth.